Length and efficiency of Italian criminal proceedings. Remarks and proposals in the light of numerical data. - Pascucci, Nicola (2020)
Italian Constitution and European Convention on Human Rights provide for the reasonable length of proceedings, although they use different expressions. First of all the Author examines this principle as objective and subjective guarantee, as well as its relations with the other constitutional guarantees of fair trial. Then he analyses the main difficulties of the current legislation to realize a speedy and fair justice, by means of official data about number and duration of criminal proceedings. In light of the practical situation, the Author formulates some reform proposals.